ANALISIS PENGELOLAAN BADAN USAHA MILIK LEMBANG (BUMLEM) DI LEMBANG TONDON LANGI’ KECAMATAN TONDON KABUPATEN TORAJA UTARA - Marniati; Ellyn Patadungan; Dyon Eka Putra; Elim Baratande (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to analyze the management of Village-Owned Enterprises (BUMLem) in Lembang Tondon Langi’, Tondon Sub-District, North Toraja Regency. This research uses a qualitative method, with data collected through interviews, observation, and documentation. The results show that the management of BUMLem in Tondon Langi’ has been running optimally. Several stages of the enterprise management process have been implemented. The management planning includes the design of activity plans, which are then compiled into a structured program, including budgeting and implementation of activities. Each activity is monitored closely by the local government to ensure smooth execution and accountability.